(untitled) (Scientific journal of the Fergana State University, 2023)
This article reveals the gnosological foundations of the formation of the moral and aesthetic qualities of future music teachers in the views of Eastern scientists on the science of music, and explores the characteristics of originality. Also, through the works of famous composers and performers, such as Borbad Marvazi, Abu Khafz Sugdi, Abu Bakr Rubabi, Abul Abbas Bakhtiyar, Abdul Kadir Marogi, Darvish Ali Changi, Pakhlavon Muhammad, Alisher Navoi, future music teachers introduced ideas of moral improvement - aesthetic quality.